The Evolution of American Legislatures: Colonies, Territories, and States, 1619-2009 - Squire, Peverill (Legislative Politics and Policy Making, 2012)
The institutional development of American legislatures, beginning with the first colonial assembly of 1619, has been marked by continuity as well as change. Peverill Squire draws upon a wealth of primary sources to document this institutional history. Beginning with the ways in which colonial assemblies followed the precedents of British institutions, Squire traces the fundamental ways they evolved to become distinct. He next charts the formation of the first state legislatures and the Constitutional Congress, describes the creation of territorial and new state legislatures, and examines the institutionalization of state legislatures in the nineteenth century and their professionalization since 1900. With his conclusion, Squire discusses the historical trajectory of American legislatures and suggests how they might further develop over the coming decades. While Squire's approach will appeal to historians, his focus on the evolution of rules, procedures, and standing committee systems, as well as member salaries, legislative sessions, staff, and facilities, will be valuable to political scientists and legislative scholars.